The code of criminal procedure - Ratanlal; Dhirajlal; Kannan, K; Prakash, Anjana (Haryana : LexisNexis, 2020)
"Ratanlal and Dhirajlal$1 (Bs criminal Procedure code is one of the country$1 (Bs most relied on and respected titles and has been in print for almost a century. The sheer fact that the book has gone through many editions, stands testimony to its intrinsic worth and Scholastic wealth. Significant changes in the well- established rules pertaining to law of crime and developments made have been referred at appropriate places in this work. Relevant statutory changes have been incorporated and important decisions by apex Courts in India, that have either altered the direction of legal principles or thrown new light on existing principles, have been carefully examined. This book is invaluable for practicing lawyers, law students, police trainees and officers, law universities, judicial academies, legal departments, judges and institutional libraries. Key features- a critical commentary covering emerging issues as well as legislative developments focuses on the developments made in the law relating to criminal law since the last publication. Traces the close inter relationship of provisions containing in Indian penal Code, code of Criminal Procedure and Indian evidence Act. Contains and discusses in detail the criminal law Amendment 2013 and 2018. Contains critical appraisal of judgments of the Indian Courts that have led to the change and development in the legal position. Major landmark and important judgements have been incorporated."--s
Keywords: India -- Criminal procedure; India -- Code of Criminal Procedure, 1973; Criminal courts